Infant mortality and low birth weight in cities of Northeastern and Southeastern Brazil Mortalidade infantil e baixo peso ao nascer em cidades do Nordeste e Sudeste, Brasil - Antônio Augusto Moura da Silva; Heloísa Bettiol; Marco Antônio Barbieri; Valdinar Sousa Ribeiro; Vânia Maria de Farias Aragão; Luiz Gustavo Oliveira Brito; Márcio Mendes Pereira (Universidade de São Paulo, 2003)
OBJECTIVE: To compare estimates of low birth weight (LBW), preterm birth, small for gestational age (SGA), and infant mortality in two birth cohorts in Brazil. METHODS: The two cohorts were performed during the 1990s, in São Luís, located in a less developed area in Northeastern Brazil, and Ribeirão Preto, situated in a more developed region in Southeastern Brazil. Data from one-third of all live births in Ribeirão Preto in 1994 were collected (2,839 single deliveries). In São Luís, systematic sampling of deliveries stratified by maternity hospital was performed from 1997 to 1998 (2,439 single deliveries). The chi-squared (for categories and trends) and Student t tests were used in the statistical analyses. RESULTS: The LBW rate was lower in São Luís, thus presenting an epidemiological paradox. The preterm birth rates were similar, although expected to be higher in Ribeirão Preto because of the direct relationship between preterm birth and LBW. Dissociation between LBW and infant mortality was observed, since São Luís showed a lower LBW rate and higher infant mortality, while the opposite occurred in Ribeirão Preto. CONCLUSIONS: Higher prevalence of maternal smoking and better access to and quality of perinatal care, thereby leading to earlier medical interventions (cesarean section and induced preterm births) that resulted in more low weight live births than stillbirths in Ribeirão Preto, may explain these paradoxes. The ecological dissociation observed between LBW and infant mortality indicates that the LBW rate should no longer be systematically considered as an indicator of social development. OBJETIVO: Comparar as estimativas das taxas de baixo peso ao nascer, prematuridade, pequeno para a idade gestacional e mortalidade infantil em duas coortes de nascimento no Brasil. MÉTODOS: As duas coortes foram realizadas na década de 90 em São Luís, localizada em uma região menos desenvolvida, no Nordeste, e em Ribeirão Preto, situada em uma região mais desenvolvida, no Sudeste. Foram coletados dados de um terço dos nascidos vivos de Ribeirão Preto, SP, em 1994 (2.839 partos únicos); em São Luís, MA, foi realizada amostragem sistemática de partos estratificada por maternidade, no período de 1997/98 (2.439 partos únicos). Os testes do qui-quadrado (categórico e para tendências) e t de Student foram usados na análise estatística. RESULTADOS: A taxa de baixo peso ao nascer foi menor em São Luís, constituindo um paradoxo epidemiológico. As taxas de prematuridade foram semelhantes, quando se esperava percentual mais elevado em Ribeirão Preto, por sua relação direta com o baixo peso ao nascer. Observou-se dissociação entre baixo peso ao nascer e mortalidade infantil, pois São Luís apresentou menor baixo peso ao nascer e maior mortalidade infantil, ocorrendo o inverso em Ribeirão Preto. CONCLUSÕES: Maior prevalência de tabagismo materno e melhor acesso e qualidade da assistência perinatal promovendo intervenções médicas mais precoces (cesárea e prematuridade induzida) que resultam em maior número de nascidos vivos com baixo peso do que natimortos em Ribeirão Preto podem explicar estas discrepâncias. A dissociação ecológica observada entre baixo peso ao nascer e mortalidade infantil sugere que a taxa daquele não deve mais ser considerada sistematicamente como indicador de desenvolvimento social.